A new species of Gymnocnemia Schneider, 1845 from Morocco with additional diagnostic data for the genus (Neuroptera, Myrmeleontidae) - Michel, Bruno (Zootaxa, 2013)
Gymnocnemia editaerevayae nov. sp. is described from the High Atlas Mountains in Morocco and compared to Gymnocnemia variegata Schneider, 1845. Descriptions of male genitalia and male and female terminalia of G. variegata are provided. Both species are illustrated.